2018
DOI: 10.1007/s00424-018-2244-7
|View full text |Cite
|
Sign up to set email alerts
|

Hibernating astronauts—science or fiction?

Abstract: For long-duration manned space missions to Mars and beyond, reduction of astronaut metabolism by torpor, the metabolic state during hibernation of animals, would be a game changer: Water and food intake could be reduced by up to 75% and thus reducing payload of the spacecraft. Metabolic rate reduction in natural torpor is linked to profound changes in biochemical processes, i.e., shift from glycolysis to lipolysis and ketone utilization, intensive but reversible alterations in organs like the brain and kidney,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 116 publications
(146 reference statements)
0
27
0
1
Order By: Relevance
“…Hibernation and cerebral hypometabolism have recently been documented in primates [dwarf lemurs (Blanco et al, 2013;Dausmann et al, 2004)], with torpor not confined solely to cold-blooded mammals. Indirectly, this implies that perhaps we humans might have the ability to hibernate, which has beneficial applications, from medicine to long-term space exploration (Chouker et al, 2019). Several species take advantage of active brain cooling (upper right inset) to induce cerebral hypometabolism consistent with the Q 10 effect, forming the basis for therapeutic hypothermia as a neuroprotective intervention in human patients after cardiac arrest/ischaemic stroke (Duan, Huber, Ding, Huber, & Geng, 2019) as 10-fold (Frerichs, Kennedy, Sokoloff, & Hallenbeck, 1994).…”
Section: Building a Better Brain; Lessons From Naturementioning
confidence: 99%
See 1 more Smart Citation
“…Hibernation and cerebral hypometabolism have recently been documented in primates [dwarf lemurs (Blanco et al, 2013;Dausmann et al, 2004)], with torpor not confined solely to cold-blooded mammals. Indirectly, this implies that perhaps we humans might have the ability to hibernate, which has beneficial applications, from medicine to long-term space exploration (Chouker et al, 2019). Several species take advantage of active brain cooling (upper right inset) to induce cerebral hypometabolism consistent with the Q 10 effect, forming the basis for therapeutic hypothermia as a neuroprotective intervention in human patients after cardiac arrest/ischaemic stroke (Duan, Huber, Ding, Huber, & Geng, 2019) as 10-fold (Frerichs, Kennedy, Sokoloff, & Hallenbeck, 1994).…”
Section: Building a Better Brain; Lessons From Naturementioning
confidence: 99%
“…Originally thought to be restricted to cold-adapted mammals, hibernation has also been observed in primates (dwarf lemurs; Blanco, Dausmann, Ranaivoarisoa, & Yoder, 2013;Dausmann, Glos, Ganzhorn, & Heldmaier, 2004), implying that perhaps we humans have the ability to hibernate, which has beneficial applications in medicine and longterm space exploration (Chouker, Bereiter-Hahn, Singer, & Heldmaier, 2019). Central metabolic roles for pyruvate dehydrogenase kinase isoenzyme 4 (Faherty, Villanueva-Canas, Blanco, Alba, & Yoder, 2018) and hibernation-specific protein (HP20 complex; Kondo et al, 2006) have been suggested as ancestral 'hibernation signatures' that contribute to mammalian brain signalling and neuroprotection.…”
Section: Building a Better Brain; Lessons From Naturementioning
confidence: 99%
“…Torpor is widespread but not ubiquitous among mammals; humans do not spontaneously enter torpor and no known interventions induce it. This is not due to phylogenetic distance from torpor species as it is described in primates, nor size as torpor can be present in bears but absent in rats [2].…”
mentioning
confidence: 69%
“…Bastide et al, 2017) and its potential to provide solutions to overcome the physiological challenges of long duration space flight (Choukèr et al, 2019;Jackson & Kochanek, 2019;Nordeen & Martin, 2019) expose the need to understand the cellular response to cooling at the molecular level. Elucidating these processes will ultimately provide solutions to pharmacologically activate beneficial pathways without the need for cooling and inactivate detrimental pathways to expand the remit of controlled cooling for medical applications.…”
Section: Discussionmentioning
confidence: 99%